1969
DOI: 10.1084/jem.130.3.619
|View full text |Cite
|
Sign up to set email alerts
|

Idiotypy of Rabbit Antibodies

Abstract: In the preceding paper (1), an answer has been given to a few of the questions raised by the idiotypy of rabbit immunoglobulins (2) with the following conclusions: that each idiotypic pattern detected in antisera against Salmonella typhi was carried by antibodies; that the antibodies of one rabbit against antigenic materials other than S. typhi did not carry the idiotypic patterns of the anti-S, typhi antibodies, or even carried definitely different idiotypic patterns; that the idiotypic specificities of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…Furthermore, the same antiserum may possess two electrophoretically distinct antibody components, each one possessing its own distinct individual antigenic specificity. These findings are in agreement with the recent studies by Nisonoff et al (28)and by Oudin et al (29,30). Furthermore, Oudin et al observed that a rabbit may produce antibodies with two or more idiotypic specificities when it is immunized with several antigens.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, the same antiserum may possess two electrophoretically distinct antibody components, each one possessing its own distinct individual antigenic specificity. These findings are in agreement with the recent studies by Nisonoff et al (28)and by Oudin et al (29,30). Furthermore, Oudin et al observed that a rabbit may produce antibodies with two or more idiotypic specificities when it is immunized with several antigens.…”
Section: Discussionsupporting
confidence: 83%
“…Each idiotypic specificity was confined to the antibody population directed against one of the immunizing antigens. On the other hand, antibodies produced in different rabbits, immunized with the same antigen, never shared the same idiotypic specificity (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the first appearance of IgG-PFC to SRBC in spleens of recipient mice injected with SRBC and normal lymphocytes was associated with clones of cells previously producing IgM (17)(18)(19). Other data are also available which indirectly support either an in vivo or in vitro switch in immunoglobulin class during differentiation (20)(21)(22)(23). Direct evidence for double producers of IgG and IgM has been reported by Nossal and coworkers (24,25), who were able to isolate cells containing both IgM and IgG.…”
Section: Discussionmentioning
confidence: 90%
“…This would suggest that, even if all the antigens in the immunizing antiserum seem to be anti-S, typhi antibodies, all the anti-S, typhi antibodies of the same rabbit, which m a y be present in a serum sample other t h a n the i m m unizing one, do not necessarily act as antigens in the precipitation reaction with the available anti-idiotypic sera. Some aspects of this particular problem will be considered in the next paper (16). I n addition, even in the anti-S, typhi serum sample used for the anti-idiotypic immunization, a part of the anti-S. typhi antibodies may not be precipitated by the anti-idiotypic sera.…”
Section: Fig 1 Reactions In Agar (Double Diffusion In Cells) a Rementioning
confidence: 99%
“…Then we will compare the idiotypic specificities of antibodies in the cases (b) where these antibodies are those of one individual against different antigens; (c) where these antibodies are those of different individuals against the same antigenic material. Other questions pertaining to the comparison of idiotypic specificities of antibodies obtained in the same individuals against S. typhi will be considered in the next paper (16). designate as anti-idiotypic immune sera or antibodies those which recognize the idiotypic specificities.…”
mentioning
confidence: 99%